Prevention and health promotion at the workplace as a part of private medical care for employees in Poland - an overview - Agata Suchańska; Andrzej Marcinkiewicz (Nofer Institute of Occupational Medicine, 2020)
This review includes information about the number of private health insurance and medical subscriptions in Poland, as well as the level of increases in premium rates, and the scale of health promotion and prevention conducted by Polish employers. The aim of this article is to present the current situation on the supplementary private medical market, which is involved in employees' healthcare, and the challenges that both employers and medical providers with health insurers are now facing, and also to present the reasons why prevention and health promotion are important factors of healthcare under private health insurance. For the purpose of this review, scientific publications devoted to health promotion at the workplace were used, along with statistical data presented in the studies released by the Polish Insurance Association, the Polish Social Security Institution, the World Health Organization and the Organization for Economic Co-operation and Development. The literature search was carried out using the electronic databases of PubMed. Search terms included medical subject headings and free text words. No year of publication restriction was imposed. The conducted analysis shows that the demand for private medical care is rising. Employers are willing to invest in private medical care for their employees, although the scale is much lower among small and medium-sized entrepreneurs due to fiscal burdens. Given the rising demand and an insufficient number of specialists, access to medical services is deteriorating, and the premium rates and costs are rising. More employers are investing in health promotion at the workplace in order to decrease absenteeism and presenteeism, lower the utilization of medical packages, and improve their attractiveness on the market. Although the interest in private medical care is rising, employers should focus on health promotion and prevention at the workplace, and adapt their actions to the employees' current needs and health issues. Med Pr. 2020;71(6):735-42